Analisis Framing Berita Humas Kanwil Kemenag Sumsel Di Website Resmi Dalam Mempertahankan Citra Institusi (Studi Kasus Berita Website Kemenag Sumsel, Periode Januari-September 2025) - Khofifah Khofifah (Journal of Innovative and Creativity, 2026)
The issue of transparency and public accountability positions government internal media as a crucial instrument in shaping institutional image and public perception. This study aims to analyze the framing strategies employed by the Public Relations Division of the Regional Office of the Ministry of Religious Affairs in South Sumatra on its official website, as well as their impact on public perception and the enhancement of human resource quality. Using Entman’s framing model (1993) integrated with Pan and Kosicki’s structural analysis, this research examines how published news is constructed, emphasizing problem definition, causal interpretation, moral evaluation, and treatment recommendation. Data were collected from news articles published between January and September 2025, focusing on three major themes: administration of the Hajj pilgrimage, social cohesion and spiritual development alongside human resource enhancement, and the promotion of halal certification to strengthen religious harmony and regional economic development. The findings indicate that the Public Relations Division consistently selects and highlights information to reinforce institutional professionalism, moral values, and public trust, demonstrating how government internal media strategically influence public perception and communicate institutional priorities effectively.